Una concepción sobre la investigación social - Rojas Guerra, José María (La Sociología en sus Escenarios, 2009)
Abstract . Ignorance or rejection of this dialectical relationship between subject and object, is in the practice of knowledge on the part of investigators, has immeasurably effects lagging behind the development of science. On the one hand, the theory leads to mysticism, and another led by the presentation of the problems of reality exclusively as a logical and methodological issues. The one and the other produces the fetishization of science. This does not exceed the investigator with the sole recognition of the dialectical relationship between subject and object, in the abstract but precisely in its human practice, in his practice as a subject it intends know about everything and foremost, through the understanding and criticism his own practice Resumen. El desconocimiento o el rechazo de esta relación dialéctica entre sujeto y objeto, tiene, en la praxis del conocimiento, por parte de los investigadores, tiene efectos inconmensurablemente retardatarios del desarrollo de la ciencia. Por un lado, induce la teoría al misticismo, y por otro induce la presentación de los problemas de la realidad, exclusivamente, como cuestiones lógicas y metodológicas. Lo uno y lo otro produce la fetichización de la ciencia. Esto no lo supera el investigador con el solo reconocimiento de la relación dialéctica entre sujeto y objeto, en abstracto sino precisamente en su práctica humana, en su práctica como sujeto que se propone conocer sobre todo y ante todo, a través de la comprensión y crítica de su propia práctica.